2018
DOI: 10.1007/jhep06(2018)116
|View full text |Cite
|
Sign up to set email alerts
|

The seven-gluon amplitude in multi-Regge kinematics beyond leading logarithmic accuracy

Abstract: Abstract:We present an all-loop dispersion integral, well-defined to arbitrary logarithmic accuracy, describing the multi-Regge limit of the 2 → 5 amplitude in planar N = 4 super Yang-Mills theory. It follows from factorization, dual conformal symmetry and consistency with soft limits, and specifically holds in the region where the energies of all produced particles have been analytically continued. After promoting the known symbol of the 2-loop N -particle MHV amplitude in this region to a function, we specia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 157 publications
7
48
0
Order By: Relevance
“…In this limit amplitudes develop large logarithms in some of the kinematic variables (1.4), and so at each loop order they reduce to a polynomial of these logarithms, the highest order of which corresponds to the leading logarithmic approximation or LLA, with an obvious generalisation to the (next-to) k -leading logarithmic approximation or N k LLA. The analysis of our four-loop amplitude provides a check of the consistency of our result with the expected structure of the Fourier-Mellin representation described in [35,37] at LLA and NLLA. It then also provides new predictions at the next two logarithmic orders.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…In this limit amplitudes develop large logarithms in some of the kinematic variables (1.4), and so at each loop order they reduce to a polynomial of these logarithms, the highest order of which corresponds to the leading logarithmic approximation or LLA, with an obvious generalisation to the (next-to) k -leading logarithmic approximation or N k LLA. The analysis of our four-loop amplitude provides a check of the consistency of our result with the expected structure of the Fourier-Mellin representation described in [35,37] at LLA and NLLA. It then also provides new predictions at the next two logarithmic orders.…”
Section: Introductionsupporting
confidence: 66%
“…In this final subsection, we will compare our findings for the 4-loop NMHV heptagon in MRK with independent results obtained for the latter to LLA [35] and NLLA [37], based on the Balitsky-Fadin-Kuraev-Lipatov (BFKL) approach [60,61,62]. We will also discuss our new predictions for the amplitude in question up to N 3 LLA.…”
Section: Comparison With Bfkl Approach and New Predictionsmentioning
confidence: 69%
See 2 more Smart Citations
“…Because R 6 (u, v, w) is totally 10 The original analyses focused on amplitudes with a one-loop leading OPE contribution. More generally, it can be shown that if the leading OPE contribution an amplitude receives is at k loops, the highest degree of logarithmic divergence is L − k [116], with k = 0 being of course maximal. symmetric, and there are only two totally symmetric quadratic polynomials, we find that that are products of just two odd zeta values (for example, (ζ 3 ) 2 in c (4) 2 ) all have vanishing coefficients.…”
Section: The Originmentioning
confidence: 99%